Modification of chromosomal architecture in human spermatozoa with large vacuoles. (9th October 2012) - Perdrix, A.; Travers, A.; Clatot, F.; Sibert, L.; Mitchell, V.; Jumeau, F.; Macé, B.; Rives, N.
Summary Human normal spermatozoa present a specific chromatin organization, illustrated particularly by the non‐random chromosome positioning. Spermatozoa with large vacuoles, described using motile sperm organelle morphology organization (MSOME), are associated with nuclear alterations, such as abnormal chromatin condensation and aneuploidy. To question a probable association between large nuclear vacuoles and chromatin disorganization, we evaluated chromosomes X, Y and 18 topography in normal spermatozoa (NS) compared with spermatozoa with large vacuoles (SLV). After centrifugation on a gradient density system, 229 NS (spermatozoa presenting a normal nuclear shape and a vacuole area <6.5% of head area) from 10 normal semen samples and 221 SLV (spermatozoa presenting a vacuole area >13% of head area) from 10 semen samples with teratozoospermia were selected using MSOME. A three‐colour FISH was carried out using α‐satellite centromeric probes for chromosomes X, Y and 18. For each chromosome, longitudinal and spatial positioning of centromeres was analysed. Distribution of each chromosome was non‐random in NS and in SLV, whatever the methodology used. Using longitudinal positioning, distribution of chromosome 18 and chromosome Y centromeres did not differ significantly between SLV and NS. On the contrary, chromosome X centromeres were more frequently positioned in the posterior region of sperm nucleus in SLV (p = 0.01). Considering spatial positioning, distributions differed significantly between SN and SLV for chromosome Y (p = 0.02) and chromosome 18 (p < 10−4) and marginally for chromosome X (p = 0.08). Our study concluded to a modification in chromosomes X, Y and 18 centromere topography between NS and SLV, representing a novel and supplementary evidence to argue chromatin disorganization in SLV.